2021
DOI: 10.1556/2006.2021.00033
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 lockdown on gambling habit: A cross-sectional study from Italy

Abstract: Background and aimsFew preliminary studies have shown an impact of COVID-19 confinement on gambling habits. We aim to evaluate short-term effects of lockdown restrictions on gambling behaviors in Italy.MethodsWithin the project Lost in Italy, a web-based cross-sectional study was conducted on a representative sample of 6,003 Italians aged 18–74 years, enrolled during April 27–May 3 2020, and were asked to report gambling activity before the lockdown and at the time of interview.ResultsThe prevalence of partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…Although several studies reported that participants might have experienced elevated self-perceived frequency of the examined behaviors based on retrospective assessment techniques ( Håkansson, 2020 ; Gainsbury et al, 2021 ; Lugo et al, 2021 ; Sallie et al, 2021 ; Wardle et al, 2021 ), it seems that “hard data” and participants’ perception of their own behaviors do not completely overlap ( Auer et al, 2020 ; Auer and Griffiths, 2021 ). Due to potential recall bias ( Schmier and Halpern, 2004 ; Hipp et al, 2020 ), findings based on repeated measurements have stronger evidential values than studies using retrospective reports (i.e., asking participants to think back and report their use – frequency or symptom severity – at pre-pandemic times).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies reported that participants might have experienced elevated self-perceived frequency of the examined behaviors based on retrospective assessment techniques ( Håkansson, 2020 ; Gainsbury et al, 2021 ; Lugo et al, 2021 ; Sallie et al, 2021 ; Wardle et al, 2021 ), it seems that “hard data” and participants’ perception of their own behaviors do not completely overlap ( Auer et al, 2020 ; Auer and Griffiths, 2021 ). Due to potential recall bias ( Schmier and Halpern, 2004 ; Hipp et al, 2020 ), findings based on repeated measurements have stronger evidential values than studies using retrospective reports (i.e., asking participants to think back and report their use – frequency or symptom severity – at pre-pandemic times).…”
Section: Discussionmentioning
confidence: 99%
“…There is a large body of cross-sectional survey studies conducted during the pandemic, working with retrospective methods (i.e., asking participants to think back to the pre-pandemic times and comparing it to current use) regarding the frequency of the given behavior (e.g., Håkansson, 2020 ; Gainsbury et al, 2021 ; Lugo et al, 2021 ; Sallie et al, 2021 ; Wardle et al, 2021 ). However, there is a relative lack of longitudinal studies.…”
Section: Introductionmentioning
confidence: 99%
“…Other details of the study and sampling methodology are provided elsewhere. 8 Recruited subjects filled an online self-administered questionnaire, including detailed information on demographic and socio-economic characteristics, such as marital status, education, number of rooms, and number of people living at home. From the number of rooms and the number of people at home, we derived the ratio of household inhabitants per room.…”
Section: Methodsmentioning
confidence: 99%
“…Available data on the impact of NPIs on health are inconsistent and inconclusive: cross-sectional assessments generally suggest an overall detrimental role of the pandemic and restrictions on lifestyles, mental health, and addictions [13] , [14] . Our previous studies on a representative sample of Italian households [15] showed huge implications on mental health symptoms [16] , smoking habits [17] , addictive behaviours [18] , and sexual activity [19] .…”
Section: Introductionmentioning
confidence: 99%